KNOWLEDGE SHARING ROLES IN DEVELOPING INNOVATION CAPABILITY IN ORDER TO IMPROVE INDIVIDUAL PERFORMANCE: (Study at Micro, Small, and Medium Enterprises guided by Surabaya City Trade Service) - Bagus Rio Prasetya Wardhana (Fakultas Ekonomi Universitas 45 Surabaya, 2018)
This research aims to analyze knowledge sharing roles in developing innovation capability in order to improve individual performance. This research uses causal research type by quantitative approach. The samples used in this research are 50 businessmen of Micro, Small, and Medium Enteprises guided by Surabaya City Trade Service. Data collection is conducted by spreading questionnaires. The data analysis technique used is SEM analysis by PLS program aid. The results in this research show that: (1) There are significant influences of knowledge sharing toward individual performance in Micro, Small, and Medium Enterprises guided by Surabaya City Trade Service; (2) There are significant influences of knowledge sharing toward individual performance in Micro, Small, and Medium Enterprises guided by Surabaya City Trade Service; (3) There are significant influences of innovation capability toward individual performance in Micro, Small, and Medium Enterprises guided by Surabaya City Trade Service.